Optical fibers on medical instrumentation: a review - Carmo, João Paulo Pereira (2014)
This paper provides a revision with the state-of-the-art related to the use of optical fiber sensors on medical instrumentation. Two types of optical fiber sensors are the focus of review: conventional optical fibers for communications and fiber Bragg gratings (FBGs).